2011
DOI: 10.1037/a0023079
|View full text |Cite
|
Sign up to set email alerts
|

Response rates track the history of reinforcement times.

Abstract: When conditioning involves a consistent temporal relationship between the conditioned stimulus (CS) and unconditioned stimulus (US), the expression of conditioned responses within a trial peaks at the usual time of the US relative to the CS. Here we examine the temporal profile of responses during conditioning with variable CS-US intervals. We conditioned stimuli with either uniformly distributed or exponentially distributed random CS-US intervals. In the former case, the frequency of each CS-US interval withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…This seems to be the case (Millenson, Allen, & Pinker, 1977;Plonsky, Driscoll, Warren, & Rosellini, 1984). Consistent with this inference, Harris, Gharaei and Pincham (2011) demonstrated that response rates during a CS track the relative frequencies, not the marginal probabilities, of reinforcement. Gaps in irregular distribution are likely to be filled with adjunctive responses.…”
Section: Sessional Consumptionmentioning
confidence: 58%
“…This seems to be the case (Millenson, Allen, & Pinker, 1977;Plonsky, Driscoll, Warren, & Rosellini, 1984). Consistent with this inference, Harris, Gharaei and Pincham (2011) demonstrated that response rates during a CS track the relative frequencies, not the marginal probabilities, of reinforcement. Gaps in irregular distribution are likely to be filled with adjunctive responses.…”
Section: Sessional Consumptionmentioning
confidence: 58%
“…In all of these studies, pretraining involving intermittent pellet delivery took place immediately prior to an SID stage in the same chamber and with the same mean rate of pellet delivery. In the present experiment, rats gained prior exposure to intermittent pellet delivery some weeks before the experiment started, in somewhat different conditioning chambers, and at lower rates of pellet delivery, which were variable, with a mean interval of 150 s between pellets (Harris et al, 2011), as opposed to the fixed interpellet interval of 30 s used here. It should be noted that there was, however, no indication in the present experiment that a rat's experimental history affected classical conditioning in the pretraining stage (Stage 1) when the house light was paired with pellet delivery in the blocking condition.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four male hooded Wistar rats from the same source as in previous experiments had previously served in fiavor learning experiments involving maltodextrin, 16 of which also had prior experience in a classical conditioning experiment in which food pellets served as the unconditioned stimulus signaled by auditory and visual conditioned stimuli (Harris, Gharaei, & Pincham, 2011). This prior history was essentially the same as that of the rats used in Experiment 1.…”
Section: Subjectsmentioning
confidence: 99%
“…Rats in Group FT30 should show a systematic change in their response rate, rising across the first 30-s of the CS and then declining again beyond that time (Church et al, 1994). An interpretation of this pattern in terms of timing of the CR to the US would be confirmed by comparing Group FT30 to Group VT30, because rats in the latter group should maintain a relatively steady level of responding across the 60-s CS presentation (Harris & Carpenter, 2011;Harris, Gharaei, & Pincham, 2011). The rats in both groups were trained for 40 days, and their response rates were analyzed from the last 20 days.…”
Section: Methodsmentioning
confidence: 97%